الاستثمار في القطاع السياحي وأثره على الاستدامة البيئية - برادي، أحمد Beradi, Ahmed; شتوان، حنان Shatwan, Hanan (المركز الجامعي أمين العقال الحاج موسى أق أخموك لتامنغست - معهد الحقوق والعلوم السياسية, 2018)
This research aims to create a clear vision about investment in tourism sector in Algeria, and the possibility of achieving it in a framework of development consistent with the requirements of the environment. Like other countries, our country seeks to promote tourism through planning to invest in this field without affecting negatively the environment. Algeria is a rich country that possesses materialistic and natural wealth. If they are exploited ideally it will be a real resource for industrial tourism and become a new attraction for investment whether at the national or foreign level. There is no doubt that tourism is one of the most important sources of national income. In addition to its contribution to attracting tourism investment and other related projects. What reinforces the idea that tourism investment itself is an industry is the ability to reach the main objectives of economic development. From an environmental perspective, the adoption of tourism will inevitably constitute the environment by preserving its natural characteristics and protecting it from any negative effects resulting from investment in tourism sector in a way that meets the needs of the present generation and the future generation as well.
هذا البحث يهدف إلى تكوين رؤية واضحة حول الاستثمار في قطاع السياحة في الجزائر، ومحاولة تحقيقه في إطار تنمية منسجمة مع متطلبات البيئة فبلادنا كغيرها من الدول تسعى إلى النهوض بهذا القطاع عن طريق التخطيط للاستثمار في المجال السياحي غير ضار بالبيئة، فهي تعتبر من قبيل الدول التي تزخر بثروات، لو استغلت على وجه أمثل لاعتبرت موردا حقيقيا لصناعة السياحة، ولأضحت نقطة جذب جديدة للاستثمار سواء على المستوى الوطني أو الأجنبي. ولا شك أن السياحة تعتبر من أهم مصادر الدخل الوطني، زيادة على إسهامها في جذب الاستثمارات السياحية والمشاريع الأخرى ذات الصلة، ما يعزز فكرة أن الاستثمار السياحي في حد ذاته صناعة، أو هو القدرة على تحقيق الأهداف الرئيسية للتنمية الاقتصادية. ومن منظور بيئي فان اعتماد السياحة سيشكل لا محالة حماية للبيئة من خلال المحافظة على خصائصها الطبيعية، وحمايتها من أية آثار سلبية ناتجة عن الاستثمار في القطاع السياحي، بشكل يلبي احتياجات الجيل الحاضر ويراعي أجيال المستقبل.
Keywords: السياسة الإقتصادية -- التنمية الإقتصادية -- النمو الإقتصادي -- التنمية المستدامة -- الإستثمار -- القطاع السياحي -- الأنشطة السياحية -- الجزائر -- المجتمع الجزائري -- مستخلصات الأبحاث -- الترجمة